Synthesis method‐dependent photothermal effects of colloidal solutions of platinum nanoparticles used in photothermal anticancer therapy. (7th January 2020) - Depciuch, J.; Stec, M.; Maximenko, A.; Drzymała, E.; Pawlyta, M.; Baran, J.; Parlinska‐Wojtan, M.
Abstract : One of the most common anticancer therapies is photothermal therapy (PTT). The effectiveness of PTT depends on the photosensitizer being a molecule which is toxic for the cancer cells after electromagnetic wave irradiation. Therefore, a simulation of PTT was performed in this work on two colon cancer cells (SW480 and SW620) using platinum nanoparticles (Pt NPs). Interestingly, in the literature the dependence between the synthesis method and the photothermal properties of Pt NPs was not discussed. Consequently, in this paper, we evaluated the photothermal properties of Pt NPs synthesized by two different methods: polyol (PtI NPs) and green chemistry (PtII NPs). Scanning transmission electron microscopy revealed that the size of both Pt NPs obtained was 2 nm, the NPs were not agglomerated, and that the PtII NPs were distributed on green tea supports. The selected area electron diffraction and X‐ray diffraction analysis confirmed the crystallinity of both types of Pt NPs. Fourier‐transform infrared (FTIR) spectrum of the PtII NPs showed interactions between the NPs and stretching modes for C=O groups from flavonoids and polyphenols. Therefore, these chemical compounds could be responsible for reducing Pt 4+ ions to Pt 0 . Moreover, the 3‐(4, 5‐dimethylthiazol‐2‐yl)‐5‐(3‐carboxymethoxyphenyl)‐2‐(4‐sulfophenyl)‐2H‐tetrazolium (MTS) assay showed that the PtII NPs exhibited 10% and 20% better cytotoxicity effect on SW480 and SW620 cells, than PtI NPs. The viability of cancer cells decreased when Pt NPs were used in PTT. The highest percentage of dead cells (82%) was observed for PtII NPs and 650‐nm laser irradiation. FTIR and Raman spectroscopy showed structural changes induced by both Pt NPs and laser irradiation of cells in the range corresponding to levels of DNA, phospholipids, proteins, and lipids. Moreover, the calculated photothermal conversion efficiency showed that the value of this parameter is around 35%, regardless of the synthesis method and used wavelengths. Abstract : The method of nanoparticles synthesis affects their anti‐cancer propertiesSynthesis methods of Pt NPs. Platinum nanoparticles synthesized by green chemistry have better anti‐cancer properties because they show the syntergy effect of platinum and green tea.